Music in West Africa Expressing Music, Expresing Culture. - Agawu, V. Kofi (Oxford University Press, Oxford, 2005)
RESUMEN: Autora Ruth M. Stone. Global Music Series. Oxford University Press, New York and Oxford, 2005